Evaluation of the Design and Implementation Readiness of the Balance Scorecard in Libraries - Pangri, Muzakkir; Masniar; Wader, Elisabeth; Kamarudin, Karlina; Evandi, Petrus (Journal of Industrial System Engineering and Management, 2024)
This research aims to design a performance measurement system (DSS) for libraries, specifically with a focus on implementing the Balanced Scorecard (BSC) method in Libraries. Performance measurement is very important to evaluate the extent to which an organization achieves predetermined goals. The quality of library services can be assessed through performance measurements, which provide insight into the effectiveness of activities, identify differences from established standards, and compare results with expectations. This research highlights the importance of performance evaluation in improving library services and library image. Systematic performance measurement can guide libraries, increase user productivity, reduce transaction costs, improve services, and demonstrate the library's value to stakeholders. The BSC method translates the library's vision, mission, and strategy into strategic goals and key performance indicators (KPI) in four perspectives: financial, customer, internal business, and learning and growth. This holistic and comprehensive approach ensures that strategic objectives are balanced between short and long terms as well as internal and external factors. The research results show increasing interest in evaluating the design and implementation readiness of BSC in libraries.